HUBUNGAN KREATIVITAS GURU TERHADAP KESULITAN BELAJAR SISWA KELAS VII PADA MATA PELAJARAN IPS DI SMP - Salsabila Intan Aristanti; Aisyah Nur Sayidatun Nisa (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
ABSTRACT Social Studies (IPS) learning at the junior high school level continues to face various challenges related to students’ learning difficulties. These difficulties not only affect students’ conceptual understanding but also influence their engagement throughout the learning process. In this context, teacher creativity has become an important aspect to investigate, as it is closely associated with the ability to create learning experiences that are more adaptive to students’ needs. This study was conducted to examine the relationship between teacher creativity and the learning difficulties experienced by seventh-grade students at SMP Negeri 5 Semarang. A quantitative approach with a correlational design was employed involving 72 students selected from a population of 287 through simple random sampling. Data were collected using a questionnaire that had met validity and reliability requirements and were analyzed through normality testing, linearity testing, and the Pearson Product Moment correlation test using IBM SPSS Statistics 27. The analysis yielded a correlation coefficient of 0.598 with a significance value of 0.000 (<0.05), indicating a significant relationship between the two variables. The findings suggest that learning environments supported by teacher creativity tend to be associated with reduced learning barriers among students. Therefore, fostering teacher creativity in instructional practice deserves greater attention as part of broader efforts to improve the quality of Social Studies learning and support student academic success. ABSTRAK Pembelajaran IPS di sekolah menengah pertama masih menghadapi berbagai tantangan yang berkaitan dengan kesulitan belajar siswa. Kondisi tersebut tidak hanya berdampak pada pemahaman konsep, tetapi juga memengaruhi keterlibatan siswa selama proses pembelajaran berlangsung. Dalam konteks ini, kreativitas guru menjadi salah satu aspek yang menarik untuk dikaji karena berhubungan dengan kemampuan menciptakan pengalaman belajar yang lebih adaptif terhadap kebutuhan peserta didik. Kajian ini difokuskan untuk mengidentifikasi hubungan antara kreativitas guru dan kesulitan belajar siswa kelas VII di SMP Negeri 5 Semarang. Penelitian dilaksanakan menggunakan pendekatan kuantitatif dengan desain korelasional terhadap 72 siswa yang dipilih dari populasi 287 siswa melalui teknik simple random sampling. Data diperoleh menggunakan angket yang telah memenuhi persyaratan validitas dan reliabilitas, kemudian dianalisis melalui uji normalitas, uji linearitas, serta korelasi Pearson Product Moment menggunakan IBM SPSS Statistics 27. Analisis menghasilkan koefisien korelasi sebesar 0,598 dengan nilai signifikansi 0,000 (<0,05), yang menunjukkan adanya hubungan signifikan antara kedua variabel. Temuan tersebut memperlihatkan bahwa pembelajaran yang didukung kreativitas guru cenderung berkaitan dengan berkurangnya hambatan belajar siswa. Oleh karena itu, pengembangan kreativitas dalam praktik pembelajaran perlu memperoleh perhatian sebagai bagian dari upaya meningkatkan kualitas proses belajar IPS di sekolah.